PENGARUH PEMBERIAN PROPOLIS LEBAH TERHADAP GAMBARAN HISTOPATOLOGI HEPAR MENCIT (Mus musculus) BETINA YANG DIPAPAR LOGAM BERAT PB ASETAT [Pb(C2H3O2)2] - Rachmani, Sartika Dewi; Safitri, Erma; Darsono, Roesno; Hestianah, Eka Pramyrtha; Plumeriastuti, Hani; Santoso, Kuncoro Puguh (Journal of Basic Medical Veterinary, 2019)
Lead acetate in the hepatobiliary system may cause peroxidation catalysis of unsaturated fatty acids, reduce nitrogenoxide and increase hydroxyl radical. Lead acetate produces oxidative stress characterized by free radical formation and inhibits lipid peroxidation. Giving antioxidants can neutralize free radicals from the detrimental effects that arise on the process or excess oxidation reactions. The purpose of this research was to find out how the effect of bee propolis on histopathologic images of hepatic mice (Mus musculus) of females exposed to lead acetate [Pb(C2H3O2)2]. The subjects were 25 mice (Mus musculus) mushulus of BALB/C strain with average weight 25-30 gram and 8 weeks old, divided into 5 treatment groups, each consisting of 5 heads per group. The K- group was given a Tween 80 solution at a doses of 0.5 mg/kgBW for 20 consecutive days. The K+ group, which was given only lead acetate at a doses of 10 mg/kgBW orally for 10 days. P1, P2, and P3 were given 10 mg/kgBW lead acetate solution orally for 10 days. The following 10 days were given bee propolis with doses of P1 200 mg/kgBW, P2 400 mg/kgBW, and P3 800 mg/kgBW. On the 21th days the mice were dissected, to observe the extent of the damage. All data were performed using a statistical test with Kruskal Wallis test and if there was a marked difference between treatment groups (p<0.05), then the Mann-Whitney test was followed. The results obtained that bee propolis can repair hepatic cell damage in mice (Mus musculus) of females exposed to lead acetate. Increased dose of bee propolis is ineffective in repairing hepatic cell damage in mice (Mus musculus) of females exposed to lead acetate.